The return of the malón: A quantitative approximation to the indigenous incursions in the Pampas - Cordero, Guido (2020)
The goal of this article is to systematize the existing information about the inter-ethnic malones in the Southern Frontier between the years of 1860 and 1875, on the eve of the so-called "conquest of the desert". We set out to identify the incursions that took place during the period, observing their occurrence in different frontier areas, the different participating leaders and groups, the amount of warriors, and the results they had regardingthe appropriation of cattle and captives. With this information, we tried to build an overview about the indigenous incursions in the totality of the frontiers. That is why we sidelined the analysis of the political dynamics characteristic of the different frontier regions, prioritizing the observation of global aspects. But it is precisely from the treatment of the borders as a whole that we can risk some hypotheses about aspects of the indigenous policies.